Pengaruh Organizational Citizenship Behavior, Lingkungan Kerja dan Stress Kerja Terhadap Kinerja Pegawai - Mochamad Irfan; Mila Hariani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to determine the influence of Organizational Civic Behavior, workplace atmosphere, and stress levels on the productivity of Social Service employees in Mojokerto Regency. This research uses quantitative methods. 50 Mojokerto Regency Social Service workers were used as research samples. Instrument testing, coefficient of determination testing, and hypothesis testing are the testing stages carried out. This research uses multiple linear regression analysis as the analysis method. The research results show that: (1) Employee performance is influenced by Organizational Citizenship Behavior (2.085) and is influenced significantly (0.043 < 0.05). Stress at work has a negative effect (-3.318) and a significant value (0.002 < 0.05), while the work environment has a positive effect (2.609) and a significant value (0.012 < 0.05). (4) work environment, work stress, and organizational citizenship behavior have a significant value (0.003 < 0.05) and a good influence (5.508) on employee performance.